2014
DOI: 10.1093/humrep/det451
|View full text |Cite
|
Sign up to set email alerts
|

Is adenomyosis associated with menorrhagia?

Abstract: The authors have no competing interests. The study was not supported by an external grant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 16 publications
5
67
3
3
Order By: Relevance
“…In addition to finding a correlation between the number of ultrasound features of adenomyosis and the degree of menstrual pain, we also found that two particular ultrasound features of adenomyosis were associated with the degree of menstrual pain: asymmetrical myometrial thickening and an irregular endometrial–myometrial junction. These individual features were also found to be significantly associated with menorrhagia. It is perhaps unsurprising that asymmetrical myometrial thickening has a greater correlation with symptoms than do other ultrasound features of adenomyosis, given that in order for this feature to be seen, the disease must have affected a significant proportion of the total myometrium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to finding a correlation between the number of ultrasound features of adenomyosis and the degree of menstrual pain, we also found that two particular ultrasound features of adenomyosis were associated with the degree of menstrual pain: asymmetrical myometrial thickening and an irregular endometrial–myometrial junction. These individual features were also found to be significantly associated with menorrhagia. It is perhaps unsurprising that asymmetrical myometrial thickening has a greater correlation with symptoms than do other ultrasound features of adenomyosis, given that in order for this feature to be seen, the disease must have affected a significant proportion of the total myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Bergeron et al suggested that it might be caused by myometrial irritability and inflammation secondary to bleeding into foci of adenomyosis, but this has yet to be proven. It may be secondary to the increased menstrual loss reported by women with adenomyosis. Zhang et al studied the presence of particular types of nerve fibers in women with adenomyosis and painful fibroids and concluded that PGP9.5‐immunoactive nerve fibers may play a role in pain generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these papers specifically look at dysmenorrhea, the most disabling symptom [11, 16, 17]. There is also a lack of consensus in the literature regarding the relationship between adenomyosis and heavy menstrual bleeding [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Heavy menstrual bleeding is the most frequent fibroid-related symptom, resulting in reduced quality of life and anemia (5), and it can be related either to the location of the fibroid (submucosal) or to fibroid-related endometrial dysfunction (11). In addition, associated endometrial lesions may be present in up to 20% women with abnormal uterine bleeding, particularly adenomyosis (12)(13)(14)(15). Pretherapeutic workup should, of course, aim to identify these associated conditions, because they may require specific care.…”
mentioning
confidence: 99%